Cutaneous Metastasis in a Patient with Pancreatic Cancer - Saif, Muhammad Wasif; Brennan, Marianne; Penney, Robin; Hotchkiss, Susan; Kaley, Kristin (JOP. Journal of the Pancreas, 2011)
Pancreatic cancer is known to metastasize rapidly. Liver and peritoneum are the most common sites of metastases in pancreatic cancer, followed by lungs, bones and brain. Less common sites of metastases such as muscle, skin, heart, pleura, stomach, umbilicus, kidney, appendix, spermatic cord and prostate have also been reported in pancreatic cancer. Cutaneous metastasis mostly occurs around umbilicus. A site other than umbilicus is rarely reported. The authors report a case of multiple skin metastases in a patient with primary pancreatic cancer and review the literature. Image: Right supraclavicular area.